Relationship between gender role attitude and fertility rate in women referring to health centers in Mashhad in 2013 - Golmakani, Nahid (Iran J Nurs Midwifery Res, 2015)
BACKGROUND: Fertility rate apparently is a non-interventional behavior, but in practice, it is influenced by social values and norms in which culture and traditional beliefs play a significant role. In this regard, some studies have shown that gender roles can be associated with reproductive behaviors. With regard to the importance of annual reduction of population growth rate and its outcomes, the present study was performed to determine the relationship between gender role attitude and fertility rate in women referring to Mashhad health centers in 2013. MATERIALS AND METHODS: The present study is an analytical cross-sectional and multistage sampling study performed on 712 women. Data were collected by a questionnaire consisting of two sections: Personal information and gender role attitude questionnaire that contained two dimensions, i.e. gender stereotypes and gender egalitarianism. Its validity was determined by content validity and its reliability by internal consistency (r = 0.77). Data were analyzed by SPSS software version 16. RESULTS: Initial analysis of the data indicated that there was a significant relationship between acceptance of gender stereotypes (P = 0.008) and gender egalitarianism (P < 0.001), and fertility. There was also a direct association between acceptance of gender stereotypes and fertility rate (r = 0.13) and an indirect association between egalitarianism and fertility rate (r = −0.15). CONCLUSIONS: The results of the present study indicate that there is an association between gender role attitude and fertility. Paying attention to women's attitude is very important for successful planning in the improvement of fertility rate and population policy.